Technology application in the banking industry: matching the customers' expectations in the next millennium / Dr. Hayati Mohammad - Mohammad, Hayati (1999)
Technology changes from time to time as a result of humans' creativity, innovativeness and knowledge. This in turn will influence the environment mainly us, the users. Technology itself is an enabler or a tool to assist us in one way or the other in our daily life. When a tool has been developed it is susceptible to the users and therefore it is up to the users to benefit from it. In this trend of the digital age, technology developed or introduced has to be benefited by the users or they will be left behind and lose the edge in this competitive environment. Not only technology development affects the businesses and the economy, but also the global citizens as a whole.